Estudio de la comercialización de Tomate (Lycopersicon esculentum Mill), mediante un Muestreo aleatorio Estratificado en un sistema de Encuestas en Tarapoto - Másquez Ruidías, Elí (1998)
This study was conducted in order to analyze the characteristics of the production and marketing of tomatoes in the area of ​​Tarapoto. Determine what marketing channels generally work was performed in a period between December 1996 and August 1997. The methodology used was based on the collection of statistical information compiled by the state branch offices and the use of level surveys producers, retailers and consumers. At the level of producers surveyed 60 of those existing in the area, the amount of 50 retailers, 44 wholesalers survey was conducted. A level consumers were surveyed 113 of these. Results were mainly analyzed using graphs, charts and frequency distribution. Statistical analyzes were derived from the use of regression coefficients, correlation coefficients, and regression equation coefficients of determination, the characteristics: number of persons per household and weekly consumption of tomatoes, standard of living and weekly consumption of tomato. the current demand and its projection was estimated until 1997.